Metabolome and transcriptome analyses provide insights into the podophyllotoxin content difference in different Sinopodophyllum hexandrum provenances - Liu, Wei; Chen, Sensen; Yuan, Xiaoqiu; Zhang, Zheng; Duan, Kai; Li, Longwei (Frontiers in Plant Science, 2026)
Sinopodophyllum hexandrum is a perennial herb medicinal plant and mainly distributes in high-altitude areas. Its rhizome is a primary material source for anticancer active ingredient podophyllotoxin (PTOX) production. The PTOX content was significantly different in rhizomes of different provenances, but this formation reason remains unclear. In this study, S. hexandrum provenances of ShaanXi (SX), GanSu (GS) and Tibet (XZ) were collected from the resource nursery of S. hexandrum. Through the combined analysis of non-targeted metabolomics and transcriptomics, candidate genes, transcription factors, and transporters significantly related to the PTOX content difference were screened to reveal the formation reason of the difference in PTOX content from different provenances. The results showed that deoxypodophyllotoxin synthase (2-ODD), secoisolariciresinol dehydrogenase (SDH) and coumarate 3-hydroxylase (C3H) were essential genes that lead to the PTOX content differences in S. hexandrum from different provenances, WRKY and AP2/ERF-ERF were considered to be key transcription factors, and ABCE1 and ABCC2 were the primary transporters. The results can provide a new perspective and excellent genes for revealing the cause of the different PTOX contents in S. hexandrum from different provenances.